Fish distribution and abundance in the Sungai Sepang Besar Estuary, Selangor: influence of water physicochemical parameters / Nurul Asyikin Ya and Harinder Rai Singh - Ya, Nurul Asyikin; Singh, Harinder Rai (Faculty of Applied Sciences, 2023)
This study reports on the abundance and distribution of seven fish species (Toxotes jaculatrix, Toxotes chatareus, Thryssa dussumieri, Plotosus lineatus, Photopectoralis bindus, Arius sagor and Stolephorus indicus) in relation to water physicochemical parameters (pH, dissolved oxygen, turbidity, salinity, temperature, ammonia, nitrogen and phosphate) of Sungai Sepang Besar (SSB) estuary. Fishes were sampled from April 2014 to February 2015 by utilizing gill nets of various mesh sizes (1.25, 2.25, 2.50, 2.75, 3, and 4.5 inches) and long lines at nine stations (S1-S9) divided into three reaches (lower, middle and upper). Dissolved oxygen (DO), salinity, pH, and ammonia were significantly different from sampling stations (p<0.05). Fish distribution in SSB was influenced by salinity, pH, DO, turbidity, phosphate, ammonia, and nitrate. Fish distribution at the lower reaches was strongly influenced by DO, salinity, turbidity, and pH; ammonia and phosphate at the upper reaches; and nitrate at the middle reaches. The findings of this study will be helpful in the management of SSB and its estuary, as well as how land use activities may impact its aquatic environment.